Mass balance of silica in straw from the perspective of silica reduction in straw pulp - Celil Atik; Saim Ates (BioResources, 2012)
The high silica content of wheat straw is an important limiting factor for straw pulping. High silica content complicates processing and black liquor recovery, wears out factory installations, and lowers paper quality. Each section of wheat straw has different cells and chemical compositions and thus different silica content. In this work, the silica content of balled straw samples were examined according to their physical components, including internodes, nodes, leaves (sheath and blade), rachis, grain, other plant bodies, and other plant spikes. Mass distribution of silica was determined by a dry ashing method. Half (50.90%) of the silica comes from leaves, and its mechanical separation will reduce the silica content in wheat straw pulp significantly. Destroying silica bodies by sonication will increase the strength properties of straw pulp.
Keywords: Phytolith; Silica; Desilication; Ash; Wheat straw; TP248.13-248.65; Biotechnology